Pengaruh Fear of Missing Out (Fomo) dan Gaya Hidup Digital Terhadap Manajemen Keuangan Mahasiswa Gen Z di Universitas Teuku Umar - Ema Rahma Yanda; Muzakir Muzakir; Rusdi Rusdi (Jurnal Ilmu Sosial dan Humaniora, 2026)
This quantitative research seeks to investigates the impact of the Fear of Missing Out (FOMO) and digital habits on the financial management of Generation Z students at Teuku Umar University during the 2025/2026 academic year. Driven by the rapid growth of social media and digital technology, the research evaluates how these contemporary factors influence students' financial decisions. Using a proportionate stratified random sampling technique and Slovin's formula, data were collected via Likert-scale questionnaires from a sample of 99 students out of a total population of 9,056. The data underwent comprehensive analysis using SPSS, which included multiple linear regression and hypothesis testing. The results reveal that FOMO and digital lifestyles have a significant and positive impact on students' financial management practices of Generation Z students at Teuku Umar University, both on their own and together. This underscores that psychological influences and the shift toward digital lifestyles play a role in shaping students' financial management behaviours. Thus, it is hoped that students will engage with social media and digital tools thoughtfully to ensure effective financial management in this digital age.